Standstill agreements, privately negotiated stock repurchases, and the market for corporate control - Dann, Larry Y.; DeAngelo, Harry (Journal of Financial Economics, 1983)
Standstill agreements are voluntary contracts which limit a substantial stockholder's ownership interest in a corporation for a specified number of years. They are often accompanied by repurchase of the substantial stockholder's shares at a premium above the market price. Standstills and premium buybacks reduce competition for corporate control and provide differential treatment of large block stockholders. The analysis indicates a statistically significant negative average effect on non-participating stockholder wealth associated with standstill agreements. Negotiated premium repurchases are also associated with negative, but less significant, stockholder returns. The evidence is inconsistent with the hypothesis that these management actions are in the best interests of non-participating stockholders.